BRAND IMAGE AND PROMOTION ON LOYALTY THROUGH CUSTOMER SATISFACTION AT FLEX GYM & CAFE - Milasari Milasari; Farah Nur Syafi’ah Wijayanti (IJMA (Indonesian Journal of Management and Accounting), 2025)
In the current era, many gyms strive to build brand image and implement effective promotion strategies to attract customer attention and establish long-term relationships, ultimately creating customer loyalty. This study aims to analyze the influence of brand image and promotion on gym member customer loyalty mediated by customer satisfaction at Flex Gym and Cafe using the Service Dominant Logic Theory. The novelty of this research lies in the selection of variables tailored to the research needs, as well as the specific location and sample size.  This study employs a quantitative research method with a casual research design and a survey approach. The population is Flex Gym members, with a purposive sampling technique based on the following criteria: male/female, has been a member for at least 3 months, minimum age of 18 years. Primary data ere collected from 100 respondents. The analysis used Structural Equation Modelingâ€“Partial Least Squares (SEM-PLS). The results indicate that: (1) Brand image positively and significantly affects customer loyalty; (2) Brand image has a positive but not significant effect on customer satisfaction; (3) Promotion positively and significantly affects customer loyalty; (4) Promotion positively and significantly affects customer satisfaction; (5) Customer satisfaction positively and significantly affects customer loyalty; (6) Customer satisfaction positively but not significantly mediates the relationship between brand image and customer loyalty; and (7) Customer satisfaction positively but not significantly mediates the relationship between promotion and customer loyalty.